A Feasibility Study to Evaluate Changes in Urinary Metabolites after OnabotulinumtoxinA Injection for Refractory Overactive Bladder - Laura M. Tellechea; Samantha Freeman; Ilir Agalliu; Melissa A. Laudano; Sylvia O. Suadicani; Nitya Abraham (Metabolites, 2022)
Metabolomics analysis of urine before and after overactive bladder (OAB) treatment may demonstrate a unique molecular profile, allowing predictions of responses to treatment. This feasibility study aimed to correlate changes in urinary metabolome with changes in OAB symptoms after intravesical onabotulinumtoxinA (BTX-A) injections for refractory OAB. Women 18 years or older with non-neurogenic refractory OAB were recruited to complete OAB-V8 questionnaires and submit urine samples before and after 100 units intravesical BTX-A injection. Samples were submitted to CE-TOFMS metabolomics profiling. Data were expressed as percent of change from pre-treatment and were correlated with OAB-V8 score improvement. Urinary metabolite changes in the OAB-V8 groups were compared using the Kruskal–Wallis test, and associations between metabolites and OAB-V8 scores were examined using quantile regression analysis. Of 61 urinary metabolites commonly detected before and after BTX-A, there was a statistically significant decrease in adenosine and an increase in N8-acetylspermidine and guanidinoacetic acid levels associated with OAB score improvement, suggesting that intravesical BTX-A injection modifies the urinary metabolome. These urinary metabolites could provide insight into OAB pathophysiology and help identify patients who would benefit most from chemodenervation.